2022
DOI: 10.1038/s41598-022-10978-3
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of responders to atropine 0.01% as treatment in Asian myopic children

Abstract: Recently, low-concentration atropine (0.01%) has gained increased attention in controlling myopia progression with satisfying effects and minimal side effects. However, studies concerning responders to 0.01% atropine are limited. This retrospective observational cohort study aimed to determine the responder characteristics of 0.01% atropine in Asian children. One hundred forty children (aged between 3 and 15 years) receiving 0.01% atropine were analyzed for the factors influencing annual spherical equivalent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Longer axial length is associated with increased risk of vision impairment from retinal detachment, myopic macular degeneration, and choroidal neovascularization. 7,8 Given these potential complications, many treatments to control myopia are being prescribed including topical atropine, [9][10][11][12][13][14][15][16][17][18][19][20][21] soft multifocal contact lenses, [21][22][23][24] overnight orthokeratology, 21,[25][26][27][28] specialized spectacle lenses, [27][28][29] increased outdoor activity, [30][31][32] and chromatic interventions. 33,34 Recently, low-dose atropine eye drops have also been used in Hong Kong to delay the onset of myopia in some children.…”
mentioning
confidence: 99%
“…Longer axial length is associated with increased risk of vision impairment from retinal detachment, myopic macular degeneration, and choroidal neovascularization. 7,8 Given these potential complications, many treatments to control myopia are being prescribed including topical atropine, [9][10][11][12][13][14][15][16][17][18][19][20][21] soft multifocal contact lenses, [21][22][23][24] overnight orthokeratology, 21,[25][26][27][28] specialized spectacle lenses, [27][28][29] increased outdoor activity, [30][31][32] and chromatic interventions. 33,34 Recently, low-dose atropine eye drops have also been used in Hong Kong to delay the onset of myopia in some children.…”
mentioning
confidence: 99%
“…We choose 0.02% atropine as a starting dose instead of 0.01% in low-risk group based upon below reasons: (1) 0.02% atropine had a better effect on myopia progression than 0.01% atropine, but 0.02% and 0.01% atropine showed similar effects on pupil diameter and accommodative amplitude (16). (2) Our prior study showed 0.01% atropine has a 58.63% responder rate in Taiwan myopic children but has better effect in certain children whose myopia better than −1.5D and age younger than 9 years when starting atropine treatment (17). About a choice of 0.05% atropine as a starting concentration in high risk group was due to that pupil dilation by 0.05% atropine is still tolerable in children between 4 and 12 years old (18).…”
Section: Discussionmentioning
confidence: 99%
“…While controversy surrounds baseline myopia as a progression factor, these differences could potentially influence the results, given that progression seems to occur faster in cases of moderate myopia compared to mild myopia 19 , 28 . Consequently, when evaluating the efficacy of 0.01% atropine treatment in children, it is vital to approach the comparison of these outcomes with caution, considering the diverse study designs and the baseline characteristics of the participants involved 29 .…”
Section: Discussionmentioning
confidence: 99%